Cutting through the haze: will Singapore's new legislation be effective? - Ewing, J. Jackson (2016)
Singapore has passed legislation to hold actors accountable for fires causing transboundary haze. This demonstrates a new level of proactivity from a haze-affected state, and reveals both Singaporean resolve and limitations in the face of haze challenges.